KINERJA KARYAWAN DEPARTEMEN HOUSEKEEPING DI SWISS-BELHOTEL HARBOR BAY BATAM HASIL PELATIHAN KERJA - Febri Ana Parhusip; Arina Luthfini Lubis; Andri Wibowo (Puslitabmas Batam Tourism Polytecnic, 2023)
Tourism is the 3rd largest foreign exchange earner in Indonesia. Tourism in Batam City is well known at the international and national levels. Batam City itself has an increase in tourist rates of 44.35 in 2020 and 49.15 in 2021 according to (BPS, 2021). This is also very influential on the hospitality industry in Indonesia, the opportunity to build a business, especially in the hospitality industry, will greatly assist tourism travel activities in Indonesia. Housekeeping or hotel housekeeping is one of the departments that has a very important role in providing services to guests, especially in providing cleaning services, tidiness and completeness of items in guest rooms (Polii and Towoliu, 2018). In general, there is a decrease in performance which is suspected to be due to the inconsistent work training conducted at Swiss-belhotel Harbor Bay Batam and the decrease in employee motivation is influenced by several factors ranging from the level of work difficulty, skill objects, promotion opportunities, employee salaries and also appreciation of employee performance. impact on employee performance. The design of this research uses a quantitative research approach. In this study, the entire population of Swiss-belhotel Harbor Bay Batam housekeeping employees was used, totaling 18 employees. Data collection was carried out by distributing questionnaires and interviews to employees. Based on the results of data analysis, discussion, and data processing in this study, it can be concluded that the training carried out at Swiss-belhotel Harbourbay Batam has a positive and significant effect on the performance of housekeeping employees.